Analisis Indikator Keberkahan Berzakat Bagi Muzakki pada Badan Amil Zakat Nasional (BAZNAS) Kota Makassar - Danto, Andi Muhammad Jaka; Kara, Muslimin; Putra, Trisno Wardy (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
The Islamic economic system is a moderate system that values private property and its development on conditions through justified means, does not tyrannize others, and has a very close relationship with the great Islamic morals and ethics. This article will describe the zakat blessings for Muzakki at BAZNAS Makassar City. This research is a type of field research that uses a qualitative approach. The results of the study show that the Islamic economic system is a moderate system that respects private property and its development with conditions through justified means, does not tyrannize others, and has a very close relationship with the great Islamic morals and ethics. The desired justice in the Islamic economic system does not solely lie in production and how to obtain it but also in its distribution and use, or utilization.